High glucose induces phosphorylation and oxidation of mitochondrial proteins in renal tubular cells: A proteomics approach - Siripat Aluksanasuwan (2020)
© 2020, The Author(s). Mitochondrial dysfunction has been thought to play roles in the pathogenesis of diabetic nephropathy (DN). However, precise mechanisms underlying mitochondrial dysfunction in DN remained unclear. Herein, mitochondria were isolated from renal tubular cells after exposure to normal glucose (5.5 mM glucose), high glucose (25 mM glucose), or osmotic control (5.5 mM glucose + 19.5 mM mannitol) for 96 h. Comparative proteomic analysis revealed six differentially expressed proteins among groups that were subsequently identified by tandem mass spectrometry (nanoLC-ESI-ETD MS/MS) and confirmed by Western blotting. Several various types of post-translational modifications (PTMs) were identified in all of these identified proteins. Interestingly, phosphorylation and oxidation were most abundant in mitochondrial proteins whose levels were exclusively increased in high glucose condition. The high glucose-induced increases in phosphorylation and oxidation of mitochondrial proteins were successfully confirmed by various assays including MS/MS analyses. Moreover, high glucose also increased levels of phosphorylated ezrin, intracellular ATP and ROS, all of which could be abolished by a p38 MAPK inhibitor (SB239063), implicating a role of p38 MAPK-mediated phosphorylation in high glucose-induced mitochondrial dysfunction. These data indicate that phosphorylation and oxidation of mitochondrial proteins are, at least in part, involved in mitochondrial dysfunction in renal tubular cells during DN.